PRINSIP MAQASHID SYARIAH DALAM PENGELOLAAN SUMBER DAYA ALAM TAMBANG PASIR: MAQASHID SYARIAH PRINCIPLES IN MANAGING NATURAL RESOURCES OF SAND MINING - Hamdan Arief Hanif; Wiwin Hasrianti Rukmana Rahamtia (Universitas Darunnajah Jakarta, Indonesia, 2024)
Abstract Indonesia is very rich in natural resources spread throughout Indonesia. Indonesia has a variety of natural resources, one of which is the natural resource of sand mining. It is known that sand mining is a sector that has many impacts on society, government and the environment. For this reason, it is necessary to carry out this research to find out the principles of maqashid sharia regarding sand mining. This research aims to determine the management of natural resources, especially sand mining natural resources which have both positive and negative impacts based on maqashid sharia principles. The type of research used in this research is library research in the form of content analysis using normative juridical and normative syar'i approaches. The method used in this research is to look for sources related to the research title and examine these sources which can explain this research. With this research, it is hoped that sand mining will provide many benefits and reduce harm. Keywords: Natural Resources, Sand Mining, Maqashid Syariah